PENGEMBANGAN MODEL PEMBELAJARAN JARINGAN SYARAF TIRUAN TIPE SUPERVISED LEARNING SEBAGAI MEDIA PEMBELAJARAN - Haryanto Haryanto; Moh. Khairudin (Jurnal Pendidikan Teknologi dan Kejuruan, 2012)
ABSTRACTThe objective of this research to develop an artificial neural networks type of supervised learning as aninstructional media of the intelligent control systems (ICS). This instructional media to facilitate understandingof the containts of the ICS subjects. It is expected to increase the quality of course materials and learningoutcomes achievements with the viability of an instructional media. This research including need analysis, design,implementation, testing and feedback analysis of instructional media, also verified the instructional media byexperts and users. On the instructional media testing covered construction, debugging process, evaluation andimprovement, the validated media refined by experts, after that finalisation and media dessimination. Data collectingconsists observation, questionnaires, check lists, and documentations. Quantitative, descriptive and evaluative areused in this analysis. The results consist (1) the description of neural network models type of supervised learningas the instructional media on the subject of ICS. (2) systematic materials for the ICS course, and (3) improving ofoutcomes quality for student achievement.Keywords: instructional media, neural network, supervised learning